Social Inclusion Beyond Education and Work: Migrants Meaning‐Making Towards Social Inclusion - Nyström, Sofia (2023)
In public discourse, the social inclusion of migrants is often regarded as a challenge demanding migrants to increase their engagement in adapting to the new host country. Such imaginaries commonly declare migrants as being unwilling to acquire language skills and specific cultural values. In parallel, formal education is often proposed as the single most important remedy to inclusion, which generally solely implies labor market participation. However, there is a range of other, often neglected, practices that migrants themselves regard as important for their social inclusion in society. This article aims to analyze what practices are assigned meaning by newly arrived migrants in Sweden on their path toward social inclusion in the country. This is a longitudinal interview study with 19 newly arrived adult migrants that were interviewed on two occasions, three years apart. Drawing on a sociocultural perspective, we understand social inclusion as an ongoing process by which individuals become members of different communities. The result shows that important for social inclusion is access to valuable relationships and close social ties. These relations are important in all communities in which the migrants participate. The analysis illustrates three different communities, outside of formal education and employment, that migrants ascribe meaning to concerning language learning and social inclusion. These communities are sports, internships, and civil society engagements. Through its longitudinal design, this study also illustrates how migrants’ narratives and their meanings shift with time and how migrants relate to these communities over time.